Almost Sure Convergence of Weighted Sums for m-END Sequences under Sub-linear Expectations - Xili, TAN; He, DONG; Peiyu, SUN; Yong, ZHANG (Scientific Insights and Discoveries Review, 2024)
By using Rosenthal's inequality, we discussed almost sure convergence of weighted sums for -END ( -extended negatively dependent) random variable sequence with the condition of , under sub-linear expectations. Almost sure convergence of weighted sums for END sequence in the classical probability space was extended to the almost sure convergence of weighted sums for -END random variable sequence under the sub-linear expectations.